OCEAN IN WORDS: CORPUS-ASSISTED CRITICAL DISCOURSE ANALYSIS OF OCEAN ISSUES IN FRENCH MEDIA - Arawinda Nariswari Dewi; Bernandus Wahyudi Joko Santoso (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
This study aims to analyze representations of ocean issues in French media using a corpus-based discourse analysis approach. By combining Corpus-Assisted Discourse Studies (CADS) and Theo van Leeuwen’s Critical Discourse Analysis (CDA) framework, this study examines how the ocean is discursively constructed in the context of maritime issues. This study adopts Corpus-Assisted Discourse Studies (CADS) to identify lexical patterns through frequency, collocation, and concordance analysis, which are then interpreted using categories of social actor representation such as exclusion, inclusion, activation, and passivation. The research data consists of French media articles focusing on environmental and marine issues. The findings reveal 5 frequent themes in the ocean. The themes are climate crisis, threatened ecosystem, authorities, science, and resources, with the climate crisis as the most frequent, comprising 16 keywords. The sea is also predominantly portrayed as a passive actor and as an affected entity, while human agents are often excluded or represented abstractly through institutions.